2021
DOI: 10.1093/rpd/ncab045
|View full text |Cite
|
Sign up to set email alerts
|

Personal Dosimetry Using Monte-Carlo Simulations for Occupational Dose Monitoring in Interventional Radiology: The Results of a Proof of Concept in a Clinical Setting

Abstract: Exposure levels to staff in interventional radiology (IR) may be significant and appropriate assessment of radiation doses is needed. Issues regarding measurements using physical dosemeters in the clinical environment still exist. The objective of this work was to explore the prerequisites for assessing staff radiation dose, based on simulations only. Personal dose equivalent, Hp(10), was assessed using simulations based on Monte Carlo methods. The position of the operator was defined using a 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The results for some cases showed a significant difference across the three MC simulation packages. This has been observed similarly in the Swedish study [26] and possible reasons for this have been considered. One difference is a variation in the exact positioning of the field on the patient phantom, and the composition of the phantom that it used by the MC code.…”
Section: Evaluating the Clinical Requirements And Feasibility Of Real...supporting
confidence: 76%
See 3 more Smart Citations
“…The results for some cases showed a significant difference across the three MC simulation packages. This has been observed similarly in the Swedish study [26] and possible reasons for this have been considered. One difference is a variation in the exact positioning of the field on the patient phantom, and the composition of the phantom that it used by the MC code.…”
Section: Evaluating the Clinical Requirements And Feasibility Of Real...supporting
confidence: 76%
“…Our study and a similar series of measurements in Sweden [26] have shown that it is feasible to simulate doses and the PODIUM concept has merit. Many technical challenges were solved and while there were some promising results, the study revealed difficulties and further challenges to be surmounted.…”
Section: Evaluating the Clinical Requirements And Feasibility Of Real...mentioning
confidence: 53%
See 2 more Smart Citations